Perbandingan Hasil Pemodelan Aliran Satu Dimensi Unsteady Flow dan Steady Flow pada Banjir Kota - Tigor Oktaga, Andreas; Suripin, Suripin; Darsono, Suseno (Department of Civil Engineering, Diponegoro University, 2015)
One dimensional flow is often used as a flood simulation for the planning capacity of the river. Flood is a type of unsteady non-uniform flow, that can be simulated using HEC-RAS. HEC-RAS software is often used for flood modeling with a one-dimensional flow method. Unsteady flow modeling results in HEC-RAS sometimes refer to error and warning due to unstable analysis program. The stability program among others influenced bend in the river flow, the steep slope of the river bottom, and changes in cross-section shape. Because the flood handling required maximum discharge and maximum flood water level, then a steady flow is often used as an alternative to simulate the flood flow. This study aimed to determine the advantages and disadvantages of modeling unsteady non-uniform and steady non-uniform flow. The research location in the Kanal Banjir Barat, in the Semarang City. Hydraulics modeling uses HEC-RAS 4.1 and for discharge the plan is obtained from the HEC-HMS 3.5. Results of the comparison modeling hydraulics the modeling of steady non-uniform flow has a tendency water level is higher and modeling of unsteady non-uniform flow takes longer to analyze. Results of the comparison the average flood water level maximun is less than 15% (± 0,3 meters), that is 0.27 meters (13.16%) for Q50, 0.25 meters (11.56%) for Q100, dan 0.16 meters (4.73%) for Q200. So the modeling steady non-uniform flow can still be used as a companion version the modeling unsteady non-uniform flow.